Recuerdos de la conferencia del Tratado Antártico de 1959 - Pinochet de la Barra, Oscar (Estudios Internacionales, 1993)
This paper recalls, from the personal perspective of a delegate present at this Conference, the gestation and configuration of the historic Antarctic Treaty of 1959. This negotiation made it possible for the continent to be born with its own laws and personality for the benefit of all humanity. In a context of the Cold War, it is emphasized that this Treaty could only be possible thanks to a spirit of mutual support, constituting an ingenious solution that left all parties calm. Among other things, are mentioned: its causes, the difficult negotiations; the importance of article IV; the topics that were included, such as the protection of the environment; its duration and the performance of key figures.